Factors influencing the attraction of foreign direct investment to the economies of developing countries - Komilovich, Madumarov Husniddin (Goodwood Publishing, 2025)
Purpose: The author would like to thank all researchers and institutions whose empirical studies and theoretical contributions have shaped our understanding of the determinants of FDI in developing countries. We also appreciate the academic databases and journal publishers for providing open access to critical literature. Research methodology: This study uses a qualitative analytical approach based on an extensive review of 40 peer-reviewed articles (2020–2024) on foreign direct investment (FDI), emphasizing the OLI paradigm and Knowledge-Capital Model. Through thematic analysis, it identifies key determinants market size, institutional quality, and infrastructure revealing regional and sectoral variations. Results: The OLI paradigm highlights key FDI determinants, emphasizing market size, GDP growth, and skilled labor as major attractors. While low labor costs drive manufacturing FDI, high-tech sectors favor productivity and innovation. Tax incentives, resources, and strong intellectual property rights also influence investment, depending on institutional and regulatory quality. Conclusions: In developing countries, the determinants of FDI have shifted from a reliance on natural resources and low-skilled labor to a greater emphasis on skilled labor, digital infrastructure, and institutional quality. To attract high-value FDI, scholars emphasize the need for a balanced strategy that includes improving the education system, advancing digital readiness, and fostering innovation ecosystems. Limitations: This study is limited by its reliance on secondary data and qualitative analysis, which may not fully capture the dynamic, country-specific investment behaviors. Contribution: This study contributes to the FDI literature by synthesizing recent empirical findings to highlight the evolving importance of institutional quality, digital infrastructure, and human capital in developing countries.